Lymphangiomatous polyps of the palatine tonsils in childhood: A case report and review - Lugo-Machado, Juan Antonio (2021)
Background: Lymphangiomatous polyps of the palatine tonsils are rare benign lesions. This entity originates from the lymphoid stroma intermixed with parenchyma, being different from papillary hyperplasia, representing approximately 1.9% of tonsillar neoplasms. Objective: To present a case report and systematic review of the pediatric cases published in the literature. The report case: A systematic review was carried out following the PRISMA guidelines of the reports in PubMed, Elsevier, Google Scholar from 2010 to 2021. 18 articles were found of which 8 females and 10 males were found, the mean age was 14 years, in 15 lesions were unilateral. All cases reported the presence of lymphatic vessels in the histopathological exam. Conclusion: There is variability with age with a similar distribution between genders, being rare there is heterogeneity in its denomination.